Entrepreneurship in Social Work: a Professional Feature or a Chllenge? - Gevorgianienė, Violeta; Fargion, Silvia (Acta Paedagogica Vilnensia, 2012)
The competence of a social worker traditionally presupposes certain instrumental capacities – to identify needs, organize help and assess outcomes. The creative nature of the profession is often undermined. The article explores the possibility of reconciling two different competencies: the one of an entrepreneur and the other of a social worker. The authors aim to compare the values and skills required in both professional fields and, through an example of the intensive course, to offer one of educational models of the developing entrepreneurial competence.Firstly, the concept of entrepreneurship is discussed underlining the similarities between the activities in two fields: social work and entrepreneurship. It is argued that the so-called “entrepreneurial mindset” is inherently part of social work professional activities. Openness to change, capacity to identify new opportunities, take risks, tolerate failure, etc. are the main elements of entrepreneurial competence. Along with this, a person’s ability to communicate and cooperate with others, to create networks, to inspire people for a change are also components of the entrepreneurial spirit which reveals the social aspect of entrepreneurship. However, the aim of social work – to help people to overcome disrupted relations among them and their environment – requires from social workers the same capacities as those mentioned above.In the second part of the article, the authors discuss the educational preconditions for social workers’ entrepreneurial competence. The discussion is based on the description of the intensive (10 days) international courses for social work students. The aim of the courses was to create a learning environment for the development of entrepreneurial competencies. The aim of the qualitative research (participative observation) was to assess the relevance of the learning environment for their development. Three main outcomes were expected: the openness to change, ability to identify new opportunities, communication and cooperation skills. The educational paradigm appropriate for the development of these competencies was based on three aspects: solution of a real social work problem, presented by a practice institution, cooperation in an international group, and students’ leading role in the learning process. The evaluation of the courses, which was based mostly on the students’ self-reflection, revealed that most students identified in themselves the development of entrepreneurial competencies and that the learning model was favourable for developing them. The authors argue that it is necessary to include the education of entrepreneurial values and skills into social work programs as well as to articulate the abilities that are already in. The awareness of the creative nature of the profession might help upgrade its status in the country as well as to redeem the professional dignity of social workers.
Keywords: entreprise; competence; social work; identification of opportunities; intensive courses